Reuso de águas de lavagem automotiva tratadas por nanofiltração e osmose inversa - Meneguzzi, Virgínia (2024)
The high pollutant load of the effluent resulting from automotive washing activity has gained environmental prominence and raised concerns considering the increasing demand for automotive aesthetic services. The initiative of water reuse in this sector is driven as concerns about water scarcity grow and environmental regulations become stricter. In this context, the advantages of membrane filtration processes propel the use of this technology in this field. The present study aimed to verify the efficiency of a wastewater treatment system for car wash effluent using nanofiltration and reverse osmosis membranes, primarily concerning the removal of surfactants. The goal was to evaluate the possibility of reusing this water for the same purpose, considering quality standards and comparing the results with those of other authors found in the literature. Samples of the raw effluent were collected from the establishment and sent to a laboratory, serving as input for the system, operating at pressures of 7 and 10 bar. Both the treated water samples in this process (permeate) and the feed samples were analyzed according to the stipulated physicochemical parameters, also monitoring the permeate flux generated in each established situation. The obtained results were statistically tested, defining the reverse osmosis membrane and the operating pressure of 10 bar as the best operating condition, used in long-term experiments with the installation of an on-site prototype, both together and subsequently with an oil-water separator box After monitoring over eight weeks, the system removed 95.00% of the surfactants, resulting in post-treatment wastewater with a pH close to neutral (7.85 ± 0.39) and a surface tension close to that of distilled water (67.55 ± 5.18 mN/m), as well as average removal efficiencies of 99.98% for turbidity, 99.66% for color, 99.22% for electrical conductivity, 100% for total nitrogen, 98.04% for COD, 86.75% for phosphorus, 88.71% for suspended solids, and 82.43% for oils and greases. Tests conducted on vehicles confirmed that this water can be reused for the same activity without causing aesthetic damage.